Recurrent Pyogenic Cholangitis: Disease Characteristics and Patterns of Recurrence. (25th May 2013) - Koh, Ye Xin; Chiow, Adrian Kah Heng; Chok, Aik Yong; Lee, Lip Seng; Tan, Siong San; Ibrahim, Salleh
Abstract : Recurrent pyogenic cholangitis (RPC) is characterized by repeated infections of the biliary system with the formation of stones and strictures. The management aims are to treat acute cholangitis, clear the biliary ductal debris and calculi, and eliminate predisposing factors of bile stasis. Operative options include hepatectomy and biliary drainage procedures or a combination of both; nonoperative options include endoscopic retrograde cholangiopancreatography (ERCP) or percutaneous transhepatic cholangiography (PTC) guided procedures. This current study compares the operative and the nonoperative management outcomes in patients with RPC in 80 consecutive patients. In addition, we aim to evaluate our approach to the management of RPC over the past decade, according to the various degrees of severity and extent of the disease, and identify the patterns of recurrence in this complex clinical condition. Initial failure rate in terms of residual stone of operative compared with nonoperative treatment was 10.2% versus 32.3% (P = 0.020 ). Long-term failure rate for operative compared with non-operative treatment was 20.4% versus 61.3% (P = 0.010 ). Based on multivariate logistic regression, the only significant factors associated with failure were bilaterality of disease (OR: 8.101, P = 0.007 ) and nonoperative treatment (OR: 26.843, P = 0.001 ). The median time to failure of the operative group was 48 months as compared to 20 months in the nonoperative group (P < 0.010 ). Thus operative treatment is a durable option in long-term resolution of disease. Hepatectomy is the preferred option to prevent recurrent disease. However, biliary drainage procedures are also an effective treatment option. The utility of nonoperative treatment can achieve a reasonable duration of disease free interval with minimal complications, albeit inferior to operative management.